PERUBAHAN SPASIAL DAN SOSIAL-BUDAYA SEBAGAI DAMPAK MEGAURBAN DI DAERAH PINGGIRAN KOTA SEMARANG - Prihanto, Teguh (Semarang State University, 2010)
Abstract:Ã‚Â Ã‚Â Ã‚Â TheÃ‚Â researchÃ‚Â ofÃ‚Â spatialÃ‚Â andÃ‚Â socio-culturalÃ‚Â changesÃ‚Â as megaurbanÃ‚Â impactsÃ‚Â inÃ‚Â urban fringeÃ‚Â areaÃ‚Â ofÃ‚Â SemarangÃ‚Â hasÃ‚Â severalÃ‚Â aims:Ã‚Â (1)Ã‚Â toÃ‚Â discoverÃ‚Â andÃ‚Â examineÃ‚Â whatÃ‚Â factorsÃ‚Â cause megaurban process,Ã‚Â (2)Ã‚Â toÃ‚Â find a mechanism or process megaurban place, andÃ‚Â (3)Ã‚Â toÃ‚Â studyÃ‚Â the effects of the process (especially spatial, socio-cultural, economics and demography. TheÃ‚Â locationÃ‚Â ofÃ‚Â thisÃ‚Â studyÃ‚Â isÃ‚Â theÃ‚Â outskirtsÃ‚Â ofÃ‚Â Semarang.Ã‚Â TheÃ‚Â cityÃ‚Â wasÃ‚Â chosenÃ‚Â becauseÃ‚Â itÃ‚Â hasÃ‚Â a strategicÃ‚Â role.Ã‚Â ThisÃ‚Â researchÃ‚Â willÃ‚Â beÃ‚Â approachedÃ‚Â inÃ‚Â anÃ‚Â integratedÃ‚Â paradigmÃ‚Â isÃ‚Â naturalisticÃ‚Â or phenomenology.Ã‚Â ThisÃ‚Â approachÃ‚Â doesÃ‚Â notÃ‚Â meanÃ‚Â denyingÃ‚Â theÃ‚Â positivisticÃ‚Â paradigm,Ã‚Â butÃ‚Â instead attemptÃ‚Â toÃ‚Â